PERLINDUNGAN HAK WARIS ANAK ANGKAT PERSPEKTIF HUKUM ISLAM DI INDONESIA - Taqrib, Mochammad (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2014)
In this age, Islam faces huge, complicated problems that demand creative responses especially through ijtihad and its methodologies. One pace has been progressively taken by the ulama (muslim scholars) and the umaro (government) in Indonesia, namely vesting inheritance right for adopted children by the mean of wasiyah wajibah which is regulated in article 209 of Islamic Law Compilation (KHI). Such right has never been regulated before in Classical Islamic law. According to classical Islamic law, adopted children have no inheritance right because they don’t have any cognation or marital relationship with the foster parents. Considering the contribution the adopted children may have to their foster parents, the ulama and the umara in Indonesia performed ijtihad and vested inheritance rights for adopted children in KHI.However, in the course of history, the article 209 could not bring justice into reality. Why? Because adopted child (or children) could only receive less inheritance than other heirs. This case may cause injustice when the adopted child has big contribution to the foster parents.Keywords: Adopted children, foster parents, KHI, justice